An Analysis of Brazil's Situation in the The Public Attitudes toward Clean Energy (PACE) Index in regard to Nuclear Energy - Razuck, Fernando Barcellos (Brazilian Journal of Radiation Sciences, 2025)
Research on public perception of science and technology has become a relevant practice throughout the world, and public opinion and political support for nuclear technology are local and variable across countries. The Public Attitudes toward Clean Energy (PACE) Index is the world’s largest publicly released international study on what people think about nuclear energy. Surveying is conducted by Savanta, and commissioned and analysed by Radiant Energy Group, the PACE Index was set up to track support/opposition for clean energy sources, what drives those attitudes, and how institutions can better cater to what the public wants.  This paper aimed analysed the results of the PACE Index in order to evaluate the public's position in the world and in Brazil regarding the use of nuclear energy. Overall, it can be said that across the 20 countries surveyed, 46% of respondents support the use of nuclear energy and the preference for nuclear energy is larger than for onshore wind, biomass from trees, or gas with carbon capture and storage. Specifically, with regard to Brazil, it can be said that the public opposition to nuclear energy exceeds support, Reliability, Health & Safety and Climate Change are seen as an important energy attribute and the younger demographics are most supportive. In this sense, it is understood that through educational actions, scientific dissemination processes and discussions with society on the subject can help the process of public acceptance of nuclear energy. A investigação sobre a percepção pública da ciência e da tecnologia tornou-se uma prática relevante em todo o mundo, e a opinião pública e o apoio político à tecnologia nuclear são locais e variáveis ​​entre países. O Índice de Atitudes Públicas em relação à Energia Limpa (PACE) é o maior estudo internacional divulgado publicamente sobre o que as pessoas pensam sobre a energia nuclear. A pesquisa é conduzida pela Savanta e encomendada e analisada pelo Radiant Energy Group. O Índice PACE foi criado para rastrear o apoio/oposição às fontes de energia limpa, o que impulsiona essas atitudes e como as instituições podem atender melhor ao que o público deseja.  Este artigo teve como objetivo analisar os resultados do Índice PACE para avaliar a posição do público no mundo e no Brasil em relação ao uso da energia nuclear. Globalmente, pode dizer-se que nos 20 países inquiridos, 46% dos inquiridos apoiam a utilização da energia nuclear e a preferência pela energia nuclear é maior do que pela energia eólica terrestre, biomassa de árvores ou gás com captura e armazenamento de carbono. Especificamente no que diz respeito ao Brasil, pode-se dizer que a oposição pública à energia nuclear excede o apoio, a Confiabilidade, a Saúde e a Segurança e as Mudanças Climáticas são vistas como um importante atributo energético e a população mais jovem dá mais apoio. Nesse sentido, entende-se que por meio de ações educativas, processos de popularização científica e discussões com a sociedade sobre o tema podem auxiliar o processo de aceitação pública da energia nuclear.